2009
DOI: 10.1007/s10734-009-9298-6
|View full text |Cite
|
Sign up to set email alerts
|

Specific remedy for specific problem: measuring service quality in South African higher education

Abstract: This study commences a process of developing a scale for the measurement of service quality in higher education in South Africa and also examines the relationship between the measures of service quality on the one hand and some other related variables such as intention to leave the university, trust in management of the university and the overall satisfaction with the university. Using structured questionnaires, survey data was collected from students (n = 391) in two South African universities. Findings indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 39 publications
4
45
0
8
Order By: Relevance
“…Further evidence was reported in Higher Education literature by De Jager and Gbadamosi (2010), where perceived service quality was significantly correlated with students" intention to leave the university.…”
Section: Perceived Services Quality and Behavior Intentionsmentioning
confidence: 56%
“…Further evidence was reported in Higher Education literature by De Jager and Gbadamosi (2010), where perceived service quality was significantly correlated with students" intention to leave the university.…”
Section: Perceived Services Quality and Behavior Intentionsmentioning
confidence: 56%
“…On the other hand, some studies have used use a single item measure to assess overall customer satisfaction (Aydin et al, 2005;Caruana, Money, & Berthon, 2000;Ismail, Harson, Ibrahim, & Isa, 2006;de Jager & Gbadamosi, 2010;Theodorakis, Kambitsis, & Laios, 2001). In this study, student satisfaction is evaluated using a single item measure to capture overall satisfaction of students.…”
Section: Customer Satisfaction In Higher Educationmentioning
confidence: 99%
“…de Jager and Gbadamosi (2010) posit that quality of service affects students' overall experience and success of programmes as it ensures continued students' patronage. A recent study by Jiewanto et al (2012) also concluded that service quality has a positive impact on student satisfaction.…”
Section: Service Quality Customer Satisfaction and Behavioural Outcomesmentioning
confidence: 99%
“…Tam, kad aukštoji mokykla kryptingai gerintų savo paslaugų kokybę, būtina nustatyti, kokios kokybės paslaugų reikia jos klientams, kiek jie patenkinti esamu paslaugų kokybės lygiu (Gruber, Fuß, Voss, Gläser-Zikuda, 2010). Todėl aukštosioms mokykloms bū-tini instrumentai, padedantys stebėti ir vertinti studentams teikiamų paslaugų kokybę bei įtraukti studentų suvokiamos paslaugų kokybės veiksnius į šių paslaugų kokybės užtikrinimą ir gerinimą (Nadiri, Kandampully, Hussain, 2009;De Jager, Gbadamosi, 2010).…”
Section: įVadasunclassified
“…Aukštąsias mokslo institucijas užtikrinti ir gerinti savo veiklos kokybę labiausiai skatina mažėjantys studentų skaičiai, akademinį gyvenimą paliečiantys globalizacijos procesai, visuomenės reikalavimai institucijų atsakomybei ir efektyvumui, kintantys įvairių suinteresuotųjų pusių poreikiai ir lūkesčiai ir kt. (Milisiunaite, Adomaitiene, Galginaitis, 2009;Žekevičienė, 2009;De Jager, Gbadamosi, 2010). Kadangi kokybės gerinimas neįmanomas be paslaugų kokybės lygio įvertinimo suinteresuotųjų pusių požiūriu, o kokybės įvertinimas netikslingas be kokybės gerinimo, taigi abiejų šių veiklų vykdymas įgalina organizaciją užtikrinti laukiamą (sutartą) kokybę.…”
Section: Paslaugų Kokybės Vertinimo Ypatumaiunclassified